Comparative characteristic of Ukrainian and Russian tongue twisters (Literatures of the World: Poetics, Mentality and Spirituality, 2014)
The Ukrainian and Russian tongue twisters are analyzed in the article in the comparative aspect. The article defines their thematic and artistic form features. It is determined that traditional information gathered by a certain nation is integrated, bound and accumulated in the national tongue twisters: ethnic self-consciousness, historical memory, way of life and customs, symbolization of occurrences of material culture etc. Poetic value and pedagogical meaningfulness of tongue twisters do not lay in the sense load (although they reflect the material culture and value system of the nation, describe the natural phenomena etc. in a playful, fun manner). They lay in the choice and arrangement of words, pronunciation of which require a certain effort from the speaker and helps developing diction and proper articulation, increasing the standard of speech as a result.
Keywords: folklore; artistic form structure; genre; tongue twisters